2012
DOI: 10.1007/bf03404209
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of a Pandemic H1N1 Influenza Outbreak in a Remote First Nations Community in Northern Manitoba, 2009

Abstract: uring the first wave of the 2009 pandemic H1N1 influenza virus (pH1N1) in the province of Manitoba, Canada, there were 892 laboratory-confirmed cases of pH1N1; 1 of these cases, 156 (17.5%) were in northern remote First Nations communities served by nursing stations (total population 45,000) (First Nations and Inuit Health Manitoba Region, Winnipeg, Manitoba Health Surveillance and Analysis, personal communication, 2009). First Nations ethnicity has been associated with increased severity of pH1N1. 2 Health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 11 publications
1
23
0
1
Order By: Relevance
“…Participants residing in suburbs and rural areas were more likely to test positive early in the study compared with inner city residents, and this pattern changed among the subsample enrolled after November 13, 2009. This is similar to the pattern observed by geography for the province of Manitoba, whereby the northern residents experienced a high incidence of infection in the first wave of the outbreak and then a much smaller incidence in the second wave of the outbreak, believed to be due to herd immunity (14,19).…”
Section: Discussionsupporting
confidence: 85%
“…Participants residing in suburbs and rural areas were more likely to test positive early in the study compared with inner city residents, and this pattern changed among the subsample enrolled after November 13, 2009. This is similar to the pattern observed by geography for the province of Manitoba, whereby the northern residents experienced a high incidence of infection in the first wave of the outbreak and then a much smaller incidence in the second wave of the outbreak, believed to be due to herd immunity (14,19).…”
Section: Discussionsupporting
confidence: 85%
“…However, our findings are similar to a report from a remote Indigenous community in Canada that showed a similar attack rate with little difference in characteristics between laboratory confirmed and probable cases. Young children were disproportionately affected, as was the case in this outbreak 15 …”
Section: Discussionmentioning
confidence: 67%
“…Socioeconomic and cultural circumstances often determine that large families live together 11,12 . Overcrowding leads to increased transmission of the influenza virus, 13,14 resulting in high influenza attack rates in Indigenous populations internationally 11,15,16 . Aboriginal people in Australia also are known to be an at‐risk group for influenza; 2,17 however, less is known about the natural history of the influenza virus within remote Aboriginal communities.…”
mentioning
confidence: 99%
“…The sanitation conditions of villages that maintain contact with the surrounding society are a challenge for the prevention of the coronavirus infection (covid-19). The control of respiratory outbreaks among native people requires good sanitation and access to treated water (9)(10) . The reality presented in the ethnographic study conducted with the Terena ethnicity of the TI Buriti showed the lack of piped water and bathrooms in the houses (use of rustic septic tanks), and reflects the reality of many indigenous lands in Brazil (4,8) .…”
Section: Process Of Indigenization In the Tackle Of The New Coronavirmentioning
confidence: 99%